Topical Vitamin C Promotes the Recovery of Corneal Alkali Burns in Mice - Min Li; Zufeng Chen; Lin Liu; Xiaoyun Ma; Jun Zou (Journal of Ophthalmology)
Background. Vitamin C (Vc) has been found to promote corneal wound healing after alkali burns. However, the specific mechanism and functional modes are still unclear. The present study sought to assess the mechanisms of Vc function on corneal alkali burns. Methods. Eighty BALB/c mice were divided into four groups: a normal group without alkali injury (n = 10), an alkali injury group without any treatment (1-day group, n = 10), a Vc group treated with topical 10% Vc (Vc group, n = 30), and a control group treated with topical sterile water (control group, n = 30). Except in the blank control group, the alkali injuries were induced in one eye of each mouse. The mice in the treatment group were given Vc by topical application (q 1 h for 6 days), while those in the control group were given topical sterile water. The clinical evaluations, including corneal fluorescent staining, corneal opacity, and neovascularization, were assessed on days 1, 4, 7, and 10 using slit-lamp microscopy. Ten mice at each time point were sacrificed. The protein expressions in the corneas of p63, PCNA, CK3, MPO, CD31, and α-SMA were detected by immunohistochemistry to examine the corneal epithelial stem cells, corneal epithelium wound healing, corneal stroma inflammation, neovascularization, and fibrosis. Results. The scores of the corneal epithelium defects, corneal neovascularization, and corneal opacities in the Vc group were significantly decreased compared to the control group on day 10. We found that Vc promoted the activation of the corneal epithelial stem cells as shown by a higher number of p63-positive and PCNA-positive cells and an increased CK3 expression when compared with the control group p<0.001. The central corneal re-epithelialization was completed by day 10. Moreover, Vc inhibited MPO, CD31, and α-SMA expressions. These results first indicated that the frequent use of topical Vc in the first 6 days of corneal alkali burns alleviated corneal inflammatory cell infiltration, activated corneal epithelial stem cell activity, and reduced corneal neovascularization and fibrosis within 10 days. Conclusions. The study, therefore, showed the therapeutic benefits of Vc on corneal alkali burns and provided new insight into the mechanisms of Vc regulation on corneal wound healing.